La relation mère-enfant dans la dramaturgie staëlienne - JIȘA, Simona (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
The Relationship between Mother and Child in Staël’s Playwriting. The article aims to analyse the plays of Germaine de Staël Agar dans le désert, Geneviève de Brabant and La Sunamite, considered as serious dramas, brought together in the perspective of the maternal relationship. The maternal archetype follows the form of the mater dolorosa capable of the greatest sacrifices. The child is seen as being inseparable from the mother and is often an innocent victim of human sins. Passionate love as the essential coordinate of romanticism is replaced by maternal love and by the love of God. The plays have a clear moralizing value, but the pathos of declamation and the introspection, characteristic of romanticism, are well visible.